Caracterização experimental e simulação computacional das deformações induzidas na fusão e cristalização do PTFE - Sciuti, Vinicius Fiocco (2016)
Polytetrafluoroethylene (PTFE) has excellent properties such as chemical inertness and useful mechanical properties at high and low temperatures. After melt, the PTFE viscosity is so high that the extrusion and injection processing are impracticable. Alternatively, the PTFE powder is cold pressed and sintered. During the sintering, heterogeneous temperature distributions may occur because of the low thermal conductivity of PTFE and induce thermal stresses. Cracks will be initiated if such stresses exceed the failure one. Considering the raw material cost (10 US$ kg−1)) and its density (2,2 g cm−3) cracks in the sintered PTFE may cause financial losses for the manufacturing industry, which justifies the studies about this process. The main mechanisms that cause permanent strains are the crystallinity change and the closure of voids from the pressing, which makes the satisfactory modeling of the PTFE sintering be complex. This work aims to characterize the strains assigned to the crystallinity changes and develop a computational model with such mechanism concerning the sintering of PTFE parts shaped by cold pressing. An experimental apparatus for the application of optical dilatometry assisted by Digital Image Correlation (DIC) was developed and used to estimate the specific volume of the amorphous and crystalline phases during sintering. The model was implemented using the UEXPAN AbaqusTM sub routine and model’s variables were obtained from literature and / or experimentally characterized. The model was validated by an experiment with thermal gradient induced strains in a PTFE specimen and the simulation results showed good correspondence with the DIC ones. For future works, it is suggested the improvement of the model implementing the void closure mechanism and the melting and crystallization kinetics, hence, the characterization of material properties in the temperature range of the process.